Ways of seeing madness: Swartz, L. (1998) Culture and mental health: A southern African view. Cape Town: Oxford University Press. ISBN 0-19-570981-0. - van der Riet, Mary (PINS-Psychology in Society, 2026)
Leslie Swartz suggests that his book could be used as a tool to think about questions of mental health and culture. In this it is a significant contribution to the practice of mental health in the South African context. The book gives the reader an understanding of the intricacies of the practice of mental health in a context from distinct from that in which the theories and practices originally emerged. It also facilitates an understanding of how one can effect (and how practitioners are effecting) a change in the practice of mental health so that it deals with the dynamics and issues of the context of South Africa.